Pengaruh Pengelolaan Dan Pemanfaatan Dana Zakat Terhadap Tingkat Pendapatan Mustahik Pada Baznas Provinsi Sumatera Utara - Anggi Mayasari Lubis; Yenni Samri Juliati Nasution; Nurwani Nurwani (Wawasan : Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2023)
This study aims to determine the effect of the Management and Utilization of Zakat Funds on Mustahik Income Levels at BAZNAS of North Sumatra Province partially and simultaneously. This study uses a quantitative research method with an associative approach. The data collection technique used a questionnaire as well as the population and sample in this study as many as 48 people who received zakat funds at BAZNAS of North Sumatra Province using a saturated sampling technique. Data were analyzed using multiple linear regression method. The results of the research based on partial hypothesis testing show that the Zakat Fund Management variable has a negative and not significant effect on Mustahik's Income Level, with a value of -0.938 <2.0141. While the variable Utilization of Zakat Funds has a positive effect on Mustahik's Income Level, with a value of 2.822 > 2.0141. The results of the simultaneous hypothesis test show that the Management and Utilization of Zakat Funds has a significant effect on Mustahik's Income Level at BAZNAS of North Sumatra Province, with a value of 4.143 > 3.20.